2000
DOI: 10.1051/aas:2000299
|View full text |Cite
|
Sign up to set email alerts
|

Hα observations of Be stars

Abstract: Abstract. We present here the Hα spectra of 44 Be stars taken at a resolution of 0.5Å. From the spectra, different emission line parameters have been deduced. A study of the correlations between different pairs of these parameters has been made with a view to understanding the mechanisms of line formation and shaping in Be stars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 5 publications
7
40
0
Order By: Relevance
“…This length would be significantly longer than the previous ones observed in the second half of the 20th century. The present descending V/R branch also suggests -consistently with the longer cycle -that the descent Rivinius et al (2006), + data compiled from Underhill (1953), Faraggiana (1969), Gray & Marlborough (1974), Slettebak & Reynolds (1978), Andrillat & Fehrenbach (1982) Hanuschik et al (1995) and Banerjee et al (2000). b) Hα and Brγ V/R variations (defined as the ratio of the full peak intensities) during the period 1995-2010.…”
Section: Long-term V/r Variations Of Emission Linessupporting
confidence: 72%
“…This length would be significantly longer than the previous ones observed in the second half of the 20th century. The present descending V/R branch also suggests -consistently with the longer cycle -that the descent Rivinius et al (2006), + data compiled from Underhill (1953), Faraggiana (1969), Gray & Marlborough (1974), Slettebak & Reynolds (1978), Andrillat & Fehrenbach (1982) Hanuschik et al (1995) and Banerjee et al (2000). b) Hα and Brγ V/R variations (defined as the ratio of the full peak intensities) during the period 1995-2010.…”
Section: Long-term V/r Variations Of Emission Linessupporting
confidence: 72%
“…To test for other Be star characteristics in δ Sco we checked for correlations between H alpha line parameters like v sin i vs. fullwidth, v sin i vs. halfwidth, peak to continuum intensity ratio vs. equivalent width etc. (Andrillat & Fehrenbach 1982;Banerjee et al 2000;Dachs et al 1986) and found it to exhibit standard Be star behaviour.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, only the line strength of Hα is measured. Hα is observed in Be stars with a variety of profile shapes (Banerjee et al 2000), ranging from single and double peaked emission to absorption, where no identifiable emission component can be detected (i.e. the star is not currently in an emission phase).…”
Section: Methodsmentioning
confidence: 99%